K ajian Perolehan Karbon sebagai Dampak Intervensi - Sri Rahaju (Institut Pertanian Bogor (IPB University), 2008)
This study was carried out as one part of comprehensive research project aimed to increase sustainable management of forests and peatlands in Indonesia in order to increase the carbon sequestration capacity and community incomes. The specific aim of the study was to calculate total value carbon gained as impact of various interventions in area of Ex-PLG Blok A, Mentangai, Central Kalimantan. Estimation on carbon stock was conducted by Sample Plot of Measurement (PCP). The interventions in this study was cannal blocking. The study showed that activity of cannal blocking resulted in a positive impact, indicated by the present of reduction carbon rate (both above and below ground carbon), as well as carbon content by tree plantation (43,451 ha). Based on result of calculation, the amount of obtained above ground carbon stock was 14,448 ton C. Carbon stock found in the tree plantation in surrounding the cannal was 0,777 ton C. Below ground carbon stock was ranged between 550,782 ton C to 2,223,424 ton C. Total above ground and below ground carbon stock were 2,541,222.78 ton C or equal to 9,317,816.85 ton CO2.